KAJIAN LITERATUR TENTANG KETERLIBATAN ORANG TUA DALAM PEMBENTUKAN KEPERCAYAAN DIRI SISWA SEKOLAH DASAR - Adilah Riza Anindya; Tunjungsari Sekaringtyas, Endang Wahyudiana (STKIP Subang, 2025)
Education at the primary level plays a vital role in developing children's self-confidence as part of the process of character building and social-emotional skills. This study aims to examine the contribution of parents in fostering self-confidence in primary school-age children using a literature study approach. Information was collected from various secondary sources such as scientific articles and previous research results. The findings show that parenting patterns that are warm, communicative and encourage children's independence significantly support the formation of healthy self-confidence. Parents who provide emotional support, appreciation of children's efforts, and opportunities to explore, play a role in strengthening children's positive perceptions of themselves. Therefore, active parental involvement in creating a supportive family environment is a key factor in strengthening children's self-confidence from an early age.